Nilai-Nilai Etnopedagogis Pada Candi Wangkal Sidoarjo Sebagai Sumber Pendidikan Berbasis Kearifan Lokal - Prasetyo, Eko; Widodo, Wahono; Istiq'faroh, Nurul (CV. Kurnia Grup, 2024)
This research aims to explore the ethnopedagogical values contained in Wangkal Temple, Sidoarjo, and their relevance as a source of education based on local wisdom. Using qualitative descriptive methods, this research identifies and analyzes various academic sources related to ethnopedagogy and the Indonesian cultural context. The results of the analysis show that Wangkal Temple contains important values such as spirituality, togetherness, perseverance, and the use of natural resources, which have strong relevance in the character of education. Learning that focuses on local wisdom can help students develop a strong cultural identity, increase environmental awareness, and foster the values of cooperation and perseverance. This research recommends the integration of ethnopedagogical values into the education curriculum in Indonesia, so that future generations can appreciate and preserve the richness of local culture while being able to compete in a global context.